Returning to work from injury: longitudinal evidence on employment and earnings - Sarah Crichton; Steven Stillman; Dean Hyslop (Institute for the Study of Labor (IZA), 2005)
New Zealand has a unique accident insurance system that pays the direct costs of all accidental injuries and compensates workers 80% of their earnings for any time post-injury that they are unable to work. Statistics New Zealand's Linked Employer-Employee Database contains monthly information on earnings, welfare benefit income, and accident-related earnings compensation for all New Zealanders from 1999-2004. Using time receiving earnings compensation as a proxy for injury severity, we estimate the effect of injuries on employment and benefit rates, and total income by comparing the observed changes in outcomes for the injured population with matched 'control' groups of non-injured individuals. We find that injuries that result in more than 3 months of earnings compensation have negative effects on future labour market outcomes. For example, individuals who receive 4 months compensation have 2% lower employment rates and 6-8% lower monthly incomes 18 months after compensation ends compared with 18 months prior to being injured than comparable non-injured workers. The magnitude of these effects increase with injury duration; individuals who receive 10-12 months of compensation have 10-15% lower employment rates, 3-4% higher benefit receipt rates, and 14-22% lower monthly incomes. We also find evidence that longer-duration injuries have larger impacts on women, older workers, and workers with lower earnings or with less stable employment histories.
Keywords: J28; C21; J24; 330; injury; programm evaluation; matching; disability; New Zealand